ALGEBRAIC STRUCTURES AND SYNTHESIS PROTEIN: A DESCRIPTION OF GENE CAPN10 (Selecciones Matemáticas, 2016)
This article mainly informative, some ways of algebraic modeling of human genome sequences is presented, with special emphasis on describing mutations in the genes, which by modifying proteinsynthesis involve genetic diseases such as Diabetes Mellitus. Mutations as endomorphisms on an R-module, which consists of a direct sum of groups of sequences 2q37.3 gene, on the rings Z64 and Z125, where el haplotype compound for the polymorphisms SNP43, SNP19 and SNP63 occur.
Keywords: Human genome; genetics; Diabetes Mellitus